2015
DOI: 10.1002/chem.201501677
|View full text |Cite
|
Sign up to set email alerts
|

CaII‐Catalyzed Alkenylation of Alcohols with Vinylboronic Acids

Abstract: Direct alkenylation of a variety of alcohols with vinylboronic acids has been accomplished using the air-stable calcium(II) complex Ca(NTf2 )2 under mild conditions with short reaction times. For reluctant transformations, an ammonium salt was used as an additive to circumvent the reactivity issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 36 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…When looked into the literature few reports are available as depicted in Figure . These methods involve the reaction of a suitable propargyl alcohol with vinylsilanes or vinyl boronic acids . Though these methods use environmentally benign Ca(NTf 2 ) 2 as the catalyst, use of non‐readily available starting materials such as vinylsilanes and vinyl boronic acids are their limitations.…”
Section: Resultsmentioning
confidence: 99%
“…When looked into the literature few reports are available as depicted in Figure . These methods involve the reaction of a suitable propargyl alcohol with vinylsilanes or vinyl boronic acids . Though these methods use environmentally benign Ca(NTf 2 ) 2 as the catalyst, use of non‐readily available starting materials such as vinylsilanes and vinyl boronic acids are their limitations.…”
Section: Resultsmentioning
confidence: 99%
“…9 To extend the utility of Ca(NTf 2 ) 2 in the functionalization of alcohols, Gandon and co-workers reported a general, efficient, and selective sp 3 -sp 2 C-C bondforming reaction using vinylboronic acids as nucleophiles. 13 Although several methods had been described to create sp 3 -sp 2 C-C bonds from alcohols and alkenes or vinylsilanes, they were often fraught with several limitations in terms of scope or reaction conditions. 14 On the other hand, vinylboronic acids present the advantage of being readily available, easy-to-handle solids, weakly toxic, and compatible with many functional groups.…”
Section: Scheme 4 Ca(ii)-catalyzed Synthesis Of 3-benzazepines 11mentioning
confidence: 99%
“…Thus, the authors demonstrated that this method has a broad scope of applicability by giving a rapid access to a large variety of alkenes, 1,4dienes, and 1,4-enynes under mild conditions (Scheme 5). 13 An interesting feature of this methodology is that, with the exception of less reactive benzyl alcohols, the use of an ammonium salt as additive is not always required to achieve the coupling reaction, which was explained by a potential synergistic activation of the alcohol by the calcium complex and the boronic acid, which could favor the ionization process.…”
Section: Scheme 4 Ca(ii)-catalyzed Synthesis Of 3-benzazepines 11mentioning
confidence: 99%
“…In 2013, we reported the transition‐metal‐free cross‐coupling reaction of alkenylboronic acids and arylboronic acids with propargylic bromides in the presence of Cs 2 CO 3 as a base [Scheme (b)] , . Recently, Gandon and co‐workers found that the cross‐coupling reaction of propargylic alcohols with alkenylboronic acids proceeds efficiently by using Ca(NTf 2 ) 2 as a catalyst [Scheme (c)] . Herein, we report that the cross‐coupling reaction of propargylic acetates with alkenylboronic acids proceeds spontaneously to give 1,4‐enynes in good yields [Scheme (d)].…”
Section: Introductionmentioning
confidence: 99%